Validity of the multidimensional reputation perception scale in private universities - Amado-Mateus, Marelby; Guzmán Rincón, Alfredo; Juarez, Fernando; Ramos, Irene (Frontiers in Education, 2024)
University reputation is the result of the assessments that the stakeholders make of the university, especially the user of the education service, the student. The literature has shown an important impact of reputation on the student's perception of the university, and it has been related to success, competitiveness, sustainability, stakeholder decision-making and the differential of the value offer. Therefore, its evaluation has been the subject of several studies that seek to measure and assess reputation in higher education to understand how to manage it. This article evaluates the psychometric properties of the reputation scale in students at private universities in Colombia. The methodology used included an adaptation of the scale to the Spanish language, content validity analysis, reliability analysis, exploratory factor analysis and confirmatory factor analysis. The results showed the validity and reliability of the scale and, through the analyses carried out, provided evidence of the scale's robustness.